IMPORTANT ASPECTS OF FORMATION OF SPIRITUAL EDUCATION IN STUDENTS - Djumaeva Sanobar Absaatovna (American Journals, 2023)
The article talks about the formation of a new type of student personality who can act adequately in the changing socio-cultural situation, that is, in higher education systems, the student's humaneness, ability to change himself and society, and the ability to actively solve current problems of professional activity are among the important factors. This scientific article examines the importance of modern pedagogical activity in solving the above problems.
Keywords: Personality of the student, spiritual education, innovation, pedagogical technology, educational process, social culture of the student, professional skills.